Endpoint admission control architectural issues and performance. - Breslau, Lee (Computer communication review.)
The traditional approach to implementing admission control, as exemplified by the Integrated Services proposal in the IETF, uses a signalling protocol to establish reservations at all routers along the path. While providing excellent quality-of-service, this approach has limited scalability because it requires routers to keep per-flow state and to process per-flow reservation messages. In an attempt to implement admission control without these scalability problems, several recent papers have proposed various forms of endpoint admission control. In these designs, the hosts (the endpoints) probe the network to detect the level of congestion; the host admits the flow only if the detected level of congestion is sufficiently low. This paper is devoted to the study of endpoint admission control. We first consider several architectural issues that guide (and constrain) the design of such systems. We then use simulations to evaluate the performance of endpoint admission control in various settings. The modest performance degradation between traditional router-based admission control and endpoint admission control suggests that a real-time service based on endpoint probing may be viable.